Upaya Meningkatkan Hasil Belajar Matematika Siswa Kelas VII Menggunakan Model Pembelajaran Quantum Teaching - Rusnila Emmi (Journal of Elementary School (JOES), 2022)
This study entitled "Efforts to Improve Mathematics Learning Outcomes in Integer Materials for Class VII.B Students at SMP Negeri 8 Lubuklinggau by using the Quantum Teaching Learning Model". This study aims to improve mathematics learning outcomes in integers in class VII.B students at SMP Negeri 8 Lubuklinggau by using the Quantum Teaching Learning Model. This type of research is in the form of Classroom Action Research (CAR) carried out in pre-action activities, cycle one and cycle two, which consists of stages of planning, implementation, observation and reflection. The subjects of this study were class VII.B students of SMP Negeri 8 Lubuklinggau. Data was collected by using test techniques and equipped with activity observations, interviews and documentation. The data can be concluded that the average student learning outcomes pre-action is 59.3 with a percentage of completeness of 43.75%, so it is necessary to carry out cycle I. In cycle I using the Quantum Teaching model the average student learning outcomes increased to 66.75 with the percentage of completeness 56.25%. However, learning in cycle I has not achieved the desire for completeness so that cycle II learning is carried out. In cycle II, the average value of student learning outcomes has increased quite well, namely 74.38 with the percentage of completeness reaching 87.50%. The research activity was carried out only until the second cycle because the results of the class average were already above the KKM value for mathematics in class VII. The conclusion is that the use of the Quantum Teaching learning model can improve mathematics learning outcomes in the class VII.B integer material at SMP Negeri 8 Lubuklinggau. Keywords: Mathematics, Quantum Teaching, Learning Outcomes